Socialization of transparent and accountable financial management in Curug, Karawang - Isro'iyatul Mubarokah; Fety Nurlia Muzayanah (Community Empowerment, 2022)
The Curug Village Government collaborates with the Community institution in Klari District, Karawang Regency, on both physical and non-physical infrastructure programs. Good financial knowledge is required for this entity in order to create transparent and accountable financial reports. The adoption of the Law of the Republic of Indonesia Number 6 of 2014 concerning Villages increased this even further. The goal of this program is to develop a good understanding and assistance in dealing with issues regarding transparent and accountable financial management in the Curug Village apparatus. Disseminating financial management is the method used. Through this program, participants can develop a better understanding of transparency and accountability in financial management as well as alternative solutions to problems encountered.